2010
DOI: 10.1002/elan.200800005
|View full text |Cite
|
Sign up to set email alerts
|

Photomicrobial Solar and Fuel Cells

Abstract: Microbial solar cells and photomicrobial fuel cells exploit the energy of light and the activity of phototrophic microorganisms to produce electricity. Whereas microbial solar cells use light as the sole energy source, photomicrobial fuel cells degrade organic matter in the presence of light. This review gives an overview about the recent developments in the field of microbial based photobiological fuel cells and microbial solar cells. It provides an insight into possible electron transfer mechanisms and eleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(44 citation statements)
references
References 76 publications
0
44
0
Order By: Relevance
“…Introduction of photosynthetically derived oxygen to the cathode compartments of MFCs to regenerate the oxidant has previously been proposed using algal cultures (3,4,30). However, to our knowledge, only a few studies have reported on the electrochemical activity of a phototrophic biocathode (1,8,9) where photosynthetic reactions are confined to the electrode biofilm, and the CV was not reported in these studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Introduction of photosynthetically derived oxygen to the cathode compartments of MFCs to regenerate the oxidant has previously been proposed using algal cultures (3,4,30). However, to our knowledge, only a few studies have reported on the electrochemical activity of a phototrophic biocathode (1,8,9) where photosynthetic reactions are confined to the electrode biofilm, and the CV was not reported in these studies.…”
Section: Discussionmentioning
confidence: 99%
“…Although no exact matches to sequences identified from the illuminated MSC were observed in the dark MSC, Proteobacteria were prevalent on both biocathodes. Reports on spontaneously formed, nonphotosynthetic marine biocathodes (33,34) have identified a number of potential microbial catalysts as part of biofilm consortia (28,30,35). The major finding from these studies appears to be that biocathode biofilms enriched from the marine environment perform optimally as a consortium rather than in pure culture and that Proteobacteria are typically observed.…”
Section: Discussionmentioning
confidence: 99%
“…Collectively, MFCs and the newer biologically catalyzed electrochemical cells have come to be known as bioelectrochemical systems (BESs) (Rabaey et al 2007; Arechederra and Minteer 2008; Ivanov et al 2010; Manohar et al 2010; Rosenbaum and Schroder 2010). As BES research becomes more sophisticated, it appears that BESs can provide new insights into the fundamental mechanisms of electron transfer between microorganisms and solid substances.…”
Section: Introductionmentioning
confidence: 99%
“…Rosenbaum and Schroder assert that algae-based microbial solar cells and photomicrobial fuel cells exploit the energy of light and the activity of phototrophic microorganisms to produce electricity [8]. 0306 …”
Section: The Importance Of the Algae And Energy Researchmentioning
confidence: 99%